E-LEARNING BERBASIS WEB PADA SD PONDOK LABU 01 PAGI - Arfiyoni Hapsari Fatimah Putri (2020)
Pondok Labu 01 Pagi Elementary School is one of the pilot schools in the Cilandak area, South Jakarta. As a pilot school, this newly renovated school will have a computer laboratory room and internet connection. But schools still have obstacles in their learning activities, such as the limited time of teaching and learning in schools, the lack of varied learning and evaluation materials, as well as the lack of means of communication between teachers and parents of students. To overcome these obstacles, school need an online learning application in the form of web-based e-learning with the Waterfall system development method. This e-learning feature presents information about the school, presents learning material that can be uploaded by teachers and downloaded by students, and can carry out student learning evaluations online. With this e-learning expected to be able to maximize the quality of teaching and learning so as to improve student achievement, and can be a means of information between teachers and parents in educating students at school and at home so as to create a unified and harmonious learning for students.